2023
DOI: 10.1007/s40430-022-03989-8
|View full text |Cite
|
Sign up to set email alerts
|

Bath heaters using alternative heat transfer medium: a thermo-economic analysis

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Similar to the previous research, land use recommendations, new routes for natural gas pipelines and associated safe distances between pipelines and crowded and sensitive buildings (e.g., schools, hospitals, stadiums and shopping malls) will be beneficial for the most populated city in Europe (Istanbul). Additionally, more experimental studies based on heat transfer, similar to that of Delouei et al [39,40] should be done to minimize the possible risks.…”
Section: Threat Distances For Worst Case Scenariomentioning
confidence: 99%
“…Similar to the previous research, land use recommendations, new routes for natural gas pipelines and associated safe distances between pipelines and crowded and sensitive buildings (e.g., schools, hospitals, stadiums and shopping malls) will be beneficial for the most populated city in Europe (Istanbul). Additionally, more experimental studies based on heat transfer, similar to that of Delouei et al [39,40] should be done to minimize the possible risks.…”
Section: Threat Distances For Worst Case Scenariomentioning
confidence: 99%
“…In the application scenario of household water supply, a more prominent problem exists: the outlet temperature fluctuates when using the faucet, and the adjustment of the outlet temperature also has a large delay. The process of waiting for the effluent temperature to be adjusted to the appropriate temperature will result in the waste of water and power resources, and the user's experience in use will be reduced [2]. The existing systems of water temperature control in domestic environments need to be perfected.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, due to the open-loop characteristic, existing systems are not equipped with the ability to resist disturbance, which brings trouble to users when they adjust the output water temperature manually. Studies have shown that current water treatment systems have the potential to reduce energy consumption by up to 45% [2]. The problems can be solved by optimizing the control system.…”
Section: Introductionmentioning
confidence: 99%